2024
DOI: 10.1002/nano.202300157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tenofovir disoproxil fumarate loaded nanoparticles for HIV‐1 treatment

Oluwafemi Samuel Obisesan,
Lesego L. Tshweu,
Sipho Chauke
et al.

Abstract: The remarkable ability of the human immunodeficiency virus (HIV) to evade the host's immune system and conventional antiretroviral therapy, has posed significant challenges in achieving complete eradication of the virus in people living with HIV (PLWHIV). However, nanotechnology has emerged as promising avenue for addressing some of the obstacles associated with the use of antiretroviral drugs by modifying drug molecules in nanoscale dimensions. Hence, the present study explores the utilization of poly(epsilon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Growing body of evidence implicating nano-delivery particles needs urgent attention as there is increasing interest in the delivery of nanoformulated antiretroviral drugs to overcome the adverse complications. Notably, recent in-vivo and in-vitro studies have demonstrated advances and promising results have been noted when TDF-loaded nanoparticles were studied on various cell lines and rat organs for their potential application to manage HIV and associated complications [ 21 23 ]. Although, the current HIV treatment regimen in South Africa containing the preferred first-line ART combination of tenofovir disoproxil fumarate, lamivudine, and dolutegravir (TLD) has produced better treatment outcomes such as viral load suppression, enhanced immune response, and improved clinical indices [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing body of evidence implicating nano-delivery particles needs urgent attention as there is increasing interest in the delivery of nanoformulated antiretroviral drugs to overcome the adverse complications. Notably, recent in-vivo and in-vitro studies have demonstrated advances and promising results have been noted when TDF-loaded nanoparticles were studied on various cell lines and rat organs for their potential application to manage HIV and associated complications [ 21 23 ]. Although, the current HIV treatment regimen in South Africa containing the preferred first-line ART combination of tenofovir disoproxil fumarate, lamivudine, and dolutegravir (TLD) has produced better treatment outcomes such as viral load suppression, enhanced immune response, and improved clinical indices [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%